Processing of parboiled wheat noodles fortified with pulsed ultrasound pomegranate (Punica granatum L. var. Malas) peel extract - Kazemi, Milad; Karim, Roselina; Mirhosseini, Hamed; Abdul Hamid, Azizah; Tamnak, Sahar (Springer, 2016)
The main objective of this study was to improve the antioxidant properties of parboiled wheat noodles (salted and yellow alkaline noodles) by adding different concentrations of pomegranate peel extract (PPE) into the noodle formulations (0, 0.75, and 1.50%) in order to produce the acceptable new product. The total phenolic contents and 2,2-diphenyl-1-picrylhydrazyl (DPPH) radical scavenging activity varied from 4.07 to 8.61 mg GAE/g and from 23.20 to 95.16%, respectively. The white salted noodle fortified with 1.50% PPE had the highest antioxidant activity among all prepared noodles. The fortified noodles showed significant (p ≤ 0.05) differences in terms of color and textural properties as compared to the control noodle. The fortified white salted noodles had a light brown color with a soft texture, whereas the fortified yellow alkaline noodles were substantially darker and harder than the white salted noodles. The fortified white noodles had a shorter optimum cooking time than the yellow noodles. The addition of PPE to the formulation of both noodles led to a reduction of pH. The current study revealed that the fortified noodles had more homogeneous and compact microstructure than the control noodle. There was no significant difference (p > 0.05) between the overall acceptability of both fortified noodles.